MODEL OF SERUMFERRITIN LEVEL BY DEFERASIROX AND DEFERIPRONEIN PEDIATRIC THALASSEMIC PATIENTS - Maneerat, Patcharee (Life Sciences and Environment Journal, 2017)
The objectives of this research are to construct model approximation using Serumferritin level by Deferasirox and Deferiprone in pediatric Thalassemic patients at clinical trial of Uttaradit hospital. This study is the retrospective cohort study. The statistical methodology is used multiple linear regressions. The error investigation and reliability was considered by R2adj and MSE. The results of this research found that: The post-Serum Ferritin of Deferasirox is involved with pre- Serum Ferritin and the enzymes alanine transaminase (ALT) while R2adj=0.755 and MSE=0.011.The post-Serum Ferritin of Deferiprone is associated with medical diagnosis, age, splenectomy, pre-Serum Ferritin and the enzymes aspartate transaminase (AST) while R2adj=0.506 and MSE=0.014.